Food characterization of the spotted pimelodid fish Pimelodus maculatus from a polluted urban river in Argentina - David Kuczynski; Juan Carlos Musa; Carla Lorraine MejÃas; Maria Florencia D'Alessandro (Journal of Tropical Life Science, 2015)
Â On the present study, the nourishment and the digestive system of a population of the spotted pimelodid Pimelodus maculatus LacepÃ¨de 1803 from a polluted urban river in Argentina were analyzed (Reconquista River, Buenos Aires province). The specimens are characterized by having benthic habits and an omnivore diet. In their intestinal content, a diversity of components was identified. Such components were grouped into ten alimentary items, with dietary variations according to body size while the longitude of the intestine remained proportional to standard length. Microbiological analysis in the gills, stomach and intestine showed the occurrence of Staphylococcus aureus, Escherichia coli and Salmonella sp. Fungi and yeast were also detected. Bacterial accounts were very high both in the analyzed organs as well in water samples. The ecological and sanitary significance of the identified bacteria is discussed.